Development of a GC–MS/SIM method for the determination of phytosteryl esters. (30th May 2019) - Tan, Siyuan; Niu, Yongjie; Liu, Liang; Su, Anping; Hu, Chingyuan; Meng, Yonghong
Highlights: A new GC–MS/SIM method has been developed to analyze phytosteryl esters in foods. The assay takes only ten minutes without saponification and liquid-liquid extraction. Corn germ oil, rice bran oil, and wheat germ oil were the three real food samples tested. The new method has high precision and accuracy based on the three food samples tested. This new method has great potential for application in the food industry. Abstract: A gas chromatography-mass spectrometry (GC–MS) method with selected ion monitoring (SIM) was developed and validated for identification and quantitative analysis of three phytosteryl esters, i.e., campesteryl oletate, stigmasteryl oletate and β-sitosteryl oletate. The method is simple and efficient and achieved good separation of the three phytosteryl esters in 10 min without saponification and liquid-liquid extraction. A calibration curve for the three phytosteryl esters had a correlation coefficient (R 2 ) better than 0.993. Detection limits were 0.42 mg/mL for campesteryl oletate, 0.32 mg/mL for stigmasteryl oletate and 0.80 mg/mL for β-sitosteryl oletate. The relative standard deviations (RSD) were within 5.47% for precision and stability for three edible oil samples. Recoveries were from 89.85% to 97.65% for each of the phytosteryl esters. These results suggest that the method can be used to identify and quantify the phytosteryl esters in oil samples.